1988
DOI: 10.1136/jnnp.51.7.929
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-effect relationships with carbamazepine and its epoxide on psychomotor and cognitive function in epileptic patients.

Abstract: SUMMARY A battery of psychometric tests was administered to 85 patients with epilepsy, of whom 26 were untreated, 40 received carbamazepine monotherapy and 19 took carbamazepine with another anticonvulsant. Carbamazepine alone had little effect on performance, but carbamazepine polypharmacy produced significant impairment. Increasing concentrations of carbamazepine (four tests) and its active metabolite, carbamazepine 10,1 1 epoxide (seven tests), correlated with decreasing performance in the monotherapy patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 21 publications
1
40
0
1
Order By: Relevance
“…CRT = choice reaction time (1 = recognition time; 2 = complete manoeuvre). 1 6r I both substances, the relationship with the epoxide being the more impressive (Gillham et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…CRT = choice reaction time (1 = recognition time; 2 = complete manoeuvre). 1 6r I both substances, the relationship with the epoxide being the more impressive (Gillham et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…OXC is a compound with similar anticonvulsant efficacy to CBZ, but which appears to have improved patient tolerability both with regard to allergic reactions and psychomotor impairment (Bulau etal., 1987;Dam etal., 1989;Houtkooper etal., 1987;Reinikainen etal., 1987). The latter potential advantage may be due to its lack of an epoxide metabolite, as this plays a major role in the neurotoxic side-effects associated with CBZ (Gillham et al, 1988;Patsalos et al, 1985).…”
Section: Oxc and Metabolitesmentioning
confidence: 99%
“…Carbamazepine A number of cognitive and psychomotor effects have been linked to carbamazepine [Gillham et al 1988]. A double-blind trial reported deterioration in measures of information processing speed and attention [Wesnes et al 2009].…”
Section: Phenytoinmentioning
confidence: 99%